Perceived barriers and enablers of nursing research in the Italian context: Findings from a systematic review - Scarsini Sara; Narduzzi Barbara; Cadorin Lucia; Palese Alvisa (Sciendo, 2022)
The research capacity of nurses has been reported to be still constrained in several countries, and not fully implemented in its potentiality due to a large number of factors. Despite its relevance both for clinical and public health purposes, no summary has been compiled to date regarding factors influencing the research capacity in the Italian context. Therefore, the primary aim of this review was to identify the barriers and enablers of conducting research as perceived by Italian nurses.